Knowledge and attitude among students towards HIV/AIDS patients at a dental college, Suraram, India - Rani, Vibha; Dumpala, Suguna; Shyamala, R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Clinical training is a part of curriculum for the dental students. They are trained in dental procedures, where there is a chance of exposure to HIV infection. Hence this study was conducted with an objective to assess their knowledge, attitude to treat these patients. Methods: An institutional based study was carried out among 145 dental students at Malla Reddy Dental College for Women. A questionnaire with 29 questions on knowledge, attitude and willing to treat the HIV/AIDS patients which was already used in other study was adapted. Primary outcome- knowledge and attitude was measured in percentages, proportions using SPSS version 20 and Chi-square. Results: Total subjects who had good knowledge were 71 (48.9%) and 137(94.5%) viewed needle stick injury can transmit HIV virus. 138 (98.1%) agreed that it is their moral responsibility to treat HIV/AIDS patients and risk of HIV transmission is high, hence special precautions have to be followed to treat them. Positive attitude towards HIV/AIDS patients was reported among 129(89%) of students. Chi square test showed an association between knowledge and attitude among study subjects which was statistically significant at p <0.05 level. Conclusions: Active student’s collaboration for treatment compliance of HIV/AIDS patients should be directed towards comprehensive training in the dental colleges which forms a basis for provision of appropriate, optimal dental care improving oral health related quality of life in people living with HIV.